TINGKAT MOTIVASI PETANI DALAM PENERAPAN SISTEM AGROFORESTRY - Idin Saepudin Ruhimat (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2015)
This study aims to determine farmers motivation level, factors affecting farmers motivation, and to formulate efforts to increasing farmers motivation in implementing agroforestry systems. This research was conducted in Lumbung District, Ciamis Regency, using the survey method of explanation. Data was analyzed with Structural Equation Modelling (SEM) approach using SmartPls 2.0 M3 program. The results showed: 1) the farmers motivation level in implementing agroforestry systems are still low so that land use with agroforestry system in the study area have not been able to provide optimal benefits; 2) farmers motivation level is directly influenced by the perception and the farmers capacity level and indirectly influenced by the characteristics of farmers, external suppor level, extension role and farmer groups role; 3) efforts to increase the farmers motivation can be done through capacity building and strengthening of farmers perceptions. Plantation and Forestry Service and Agricultural Service in Ciamis Regency are advised to include agroforestry program in the work plan of the agencies and facilitate the implementation of: 1) education, training and extension; 2) facilitate the development of agroforestry technology package demplot; and 3) fasilitate the implemantation of comparative study.